Conversion therapy for initially unresectable hepatocellular carcinoma using a combination of toripalimab, lenvatinib plus TACE: real-world study. Issue 5 (20th September 2022) - Qu, Wei-Feng; Ding, Zhen-Bin; Qu, Xu-Dong; Tang, Zheng; Zhu, Gui-Qi; Fu, Xiu-Tao; Zhang, Zi-Han; Zhang, Xin; Huang, Ao; Tang, Min; Tian, Meng-Xin; Jiang, Xi-Fei; et al.
Abstract: Background: Combination conversion therapies afforded curative surgery chance for initially unresectable hepatocellular carcinoma (uHCC). This study aimed to evaluate the conversion rate and clinical outcomes of a first-line conversion regimen of lenvatinib combined with transarterial chemoembolization (TACE) plus immunotherapy for initial uHCC by interpreting real-world data. Methods: Conversion therapy data of patients with uHCC from November 2018 to January 2021 were analysed. The regimens included triple combination therapy (t-CT: lenvatinib, TACE, plus toripalimab) and dual combination therapy (d-CT: lenvatinib plus TACE). Another study population diagnosed with hepatocellular carcinoma of macrovascular invasion disease were included as the upfront surgery cohort. Treatment responses and conversion rate were primary outcomes. Survival and adverse events were analysed. Results: Fifty-one patients receiving t-CT ( n = 30) and d-CT ( n = 21) were enrolled. Higher overall response rates (76.7 per cent versus 47.6 per cent, P = 0.042) and disease control rates (90.0 per cent versus 57.1 per cent, P = 0.042) were observed via t-CT than d-CT. Both median overall survival and event-free survival were not reached in the t-CT cohort. A higher rate of curative conversion resection was achieved through t-CT than d-CT (50.0 per cent versus 19.0 per cent, P = 0.039). The disease-free survival of patients undergoing conversion resection in the t-CT cohort ( n = 15) was higher than that in the upfront surgery cohort ( n = 68, P = 0.039). Both t-CT and d-CT regimens were tolerable. Conclusions: Better treatment responses and conversion rate for patients with uHCC were obtained with first-line t-CT. Neoadjuvant t-CT before surgery should be recommended for patients with macrovascular invasion. Abstract : The first-line triple combination therapy (t-CT) of transarterial chemoembolization plus anti-PD-1 antibodies plus lenvatinib increase the conversion rate and treatment responses for patients with unresectable hepatocellular carcinoma. Neoadjuvant t-CT regimen is recommended for China Liver Cancer Staging stage IIIa patients.